Deep learning enables the atomic structure determination of the Fanconi Anemia core complex from cryoEM. (2020) - Farrell, Daniel P.; Anishchenko, Ivan; Shakeel, Shabih; Lauko, Anna; Passmore, Lori A.; Baker, David; DiMaio, Frank
No abstract available